Focused strength and speed-strength trainings of sprinters - Vrublevskiy, E. P.; Khorshidakhme, Kh. S.; Albarkaii, D. A. (Theory and Practice of Physical Culture, 2019)
The modern 100m sprinters` training systems make a special emphasis on the speed-strength training component to facilitate the specific strength building in the key muscle groups for competitive success. The functional specialization of the sprinter`s musculoskeletal system shall not be driven by passive adaptation to the specific competitive requirements, with the trainees expected to attain the sport-specific musculoskeletal system anthropometrical characteristics and functionality for competitive success.